2003
DOI: 10.1148/radiol.2261011365
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Exposure during Cardiac CT: Effective Doses at Multi–Detector Row CT and Electron-Beam CT

Abstract: Higher radiation doses are delivered at multi-detector row cardiac CT compared with the doses delivered at electron-beam CT and catheter coronary angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
198
1
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 373 publications
(210 citation statements)
references
References 48 publications
3
198
1
8
Order By: Relevance
“…48 This value is approximately two to three times the patient dose during a diagnostic coronary angiogram. 48,49 Techniques have been developed to reduce the radiation dose with newer generation scanners, such as limiting x-ray emission during certain phases of image acquisition. 48 …”
Section: Artifacts and Limitationsmentioning
confidence: 99%
“…48 This value is approximately two to three times the patient dose during a diagnostic coronary angiogram. 48,49 Techniques have been developed to reduce the radiation dose with newer generation scanners, such as limiting x-ray emission during certain phases of image acquisition. 48 …”
Section: Artifacts and Limitationsmentioning
confidence: 99%
“…of typical doses encountered with CTCA have been reported 5 , including two recent reports estimating radiation dose in populations of patients under clinical practice conditions 6, 7 , there is little data addressing organ dose 8,9 and no data on the relationship between radiation dose and cancer risk in actual patients undergoing clinical CTCA examinations.…”
mentioning
confidence: 99%
“…CTA is still associated with exposure to a considerable amount of radiation dose, and thus the indications for performing CTA have to be clearly defined. 19,20 The results of this study and other single-centre studies need to be confirmed by multi-centre trials.…”
Section: Study Limitationsmentioning
confidence: 61%